2011
DOI: 10.1161/strokeaha.111.614420
|View full text |Cite
|
Sign up to set email alerts
|

Limited Ability to Activate Protein C Confers Left Atrial Endocardium A Thrombogenic Phenotype

Abstract: Background and Purpose-Atrial fibrillation is the most important risk factor for cardioembolic stroke. Thrombi form in the left atrial appendage rather than in the right. The causes of this different thrombogenicity are not well-understood. The goal herein was to compare the activation of the anticoagulant protein C and the thrombomodulin and endothelial protein C receptor/activated protein C receptor expression on the endocardium between right and left atria. Methods-We harvested the atria of 6 monkeys (Macac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Endothelial dysfunction has been implicated in the increased risk for thrombus formation within the failing heart. Given the critical endogenous anticoagulant role of APC [ 23 , 26 ], we examined APC generation on the LV endocardial surface. Our results show a striking decrease in the APC generating ability of the endocardium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endothelial dysfunction has been implicated in the increased risk for thrombus formation within the failing heart. Given the critical endogenous anticoagulant role of APC [ 23 , 26 ], we examined APC generation on the LV endocardial surface. Our results show a striking decrease in the APC generating ability of the endocardium.…”
Section: Discussionmentioning
confidence: 99%
“…This attenuation is paralleled by increased thrombin generation on the endocardial surface in acute decompensated HF mice. An attenuation of APC generation in the left atrial appendage, as compared to the right, has been postulated as a possible reason for the increased formation of thrombi within the left atria in atrial fibrillation [ 26 ]. In the latter study, however, thrombi numbers were not quantified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated protein C is one of the most potent natural anticoagulants; protein C binds to the endothelial protein C receptor where it is activated by a complex of thrombin and thrombomodulin. Cervero et al 163 reported a significant underexpression of thrombomodulin by the left as compared to the right atrial endocardium, and less than half the ability to activate protein C. In pigs with induced AF, PAI-1 protein expression was increased in the LA but not the right atrium, and the LA increase was accompanied by a decrease in nitric oxide. 164 In patients with chronic AF, thrombin generation is increased in the LA compared to the periphery.…”
Section: Atrial Myopathy and Stroke Riskmentioning
confidence: 96%
“…(PAI) 1, von Willebrand factor (vWF), and adhesion molecules (ICAM, VCAM, selectins) [5,16,20]. There is clinical evidence that AF-induced thrombogenicity of the left atrium is much greater compared with the right atrium [9]. This helps to explain why AF induces predominantly systemic emboli and stroke rather than pulmonary emboli.…”
mentioning
confidence: 99%